SMART VEST AND MONITORING SYSTEM FOR AIRSOFT SPORT-GAMES USING VIBRATION SENSOR - Mutiara, Giva Andriana; Periyadi, Periyadi; Agnas, Andry Dupti; Darma, Velly (International Journal of Computing, 2020)
Airsoft gun is a replica of weapons used for airsoft sports-games activities. These sport-games are usually equipped with ball bullet type, vest protector, helmet and sunglasses. Rules of the game are defined by prioritizing the honesty of each player if hit by a shot. This becomes a weakness and is misused by the player. To reduce these two impacts, this paper proposed an innovation by developing vest that can detect laser light and the bullet. Those hits then connected to the database and also monitoring system. This system is constructed using Light Dependent Resistor, Raspberry Pi 3, motor vibration sensor, piezoelectric, LED lamp, and buzzer. By utilizing the MAC Address of Raspberry Pi 3, the player can be recognized and the counter of the remaining lives of the player will be displayed. The player’s life can be determined by a shoot, if point 25 is set for one shoot, then the player declares the game is over after four hits. Based on the testing results, this research can help to do these sport-games informative, efficient and fairly.